Shock therapy or gradualism? : a comparative approach to anti-inflation policies : studies commissioned by the Group of Thirty, together with its policy statement, "Measures to combat inflation" ; [William Fellner ... et al.]. - Fellner, William John; Group of Thirty (New York, N.Y. : Group of Thirty, 1981)
The basic problem in the functioning of the international monetary and economic system ;concern with inflation
Includes bibliographical references.
obn 24/10/2019
Loans
Keywords: Inflation (Finance); Wage-price policy